Barriers to Access Reproductive Health Care Services by Urban Women (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Health care is a continuous care from womb to tomb. Bangladesh has made tremendous achievement in the health sector over the last few decades. Early marriage, perception about pregnancy and high financial cost are the factors for less utilization of health care services. Many other barriers like gender inequality, cultural norms and traditions are important barriers too for seeking reproductive health care services.   Objectives: To further unpack the pattern of dynamic social barriers faced by urban women in accessing reproductive health care services, which in turn may assist the service stakeholders to design programs to overcome the barriers.Materials and Methods: This is a descriptive empirical social study was executed in Dhaka city from January 2019 to April 2019. Interviewer administered face to face in depth interview was employed to collect data from 122 samples, estimated by peer review and picked up by haphazard sampling, from among married women of reproductive age 15-45years. Data were analyzed by SPSS 20. Emic and etic interpretation were done on the information generated. All ethical issues were taken care of. Results: The perceived barriers to antenatal, natal, postnatal care and family planning practices were poverty, ignorance and husband non co-operation. As many as 78.7% respondents were house wives, about 71.0% respondent’s age at marriage was 13- 18 years, 36.1% were qualified up to intermediate level, 53.3% are 25-35yrs age group, 80% received antenatal care, 32% gone for home delivery and 68.7% were unwilling for postnatal care services. The present study found that ignorance and poverty were the main reasons for non-utilizing health care facilities.Conclusion: There is scope to improve the utilization of reproductive health care services of urban women. Social and cultural barriers are more common. Health care services are needed to be scaled up and the health education component should be strengthened in health care delivery system to achieve Sustainable Development Goal (SDG).Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 7-10